2012
DOI: 10.1002/jrs.3074
|View full text |Cite
|
Sign up to set email alerts
|

Portable smart films for ultrasensitive detection and chemical analysis using SERS and SERRS

Abstract: Metallic nanostructures, much smaller than the wavelength of visible light, which support localized surface plasmon resonances, are central to the giant signal enhancement achieved in surface‐enhanced Raman scattering (SERS) and surface‐enhanced resonance Raman scattering (SERRS). Plasmonic driven SERS and SERRS is a powerful analytical tool for ultrasensitive detection down to single molecule detection. For all practical SERS applications a key issue is the development of reproducible and portable SERS‐active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…This strategy generates nanocomposites whose morphology can vary, such as in a polymeric shell and a metal core [60,61,77,96,102], a polymeric core and a metal shell [95] or a polymeric matrix having dispersed metallic fillers [68,69,97]. In particular cases, the polymer can act as reducing agent due to specific functional groups, avoiding the use of an external reducing agent [61,73]. The advantages of this one-step approach relies on its simplicity, although the resulting nanocomposites may exhibit inhomogeneity in terms of morphology and fillers distribution in the polymer matrix [10,129].…”
Section: Chemical Reduction (In Situ Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy generates nanocomposites whose morphology can vary, such as in a polymeric shell and a metal core [60,61,77,96,102], a polymeric core and a metal shell [95] or a polymeric matrix having dispersed metallic fillers [68,69,97]. In particular cases, the polymer can act as reducing agent due to specific functional groups, avoiding the use of an external reducing agent [61,73]. The advantages of this one-step approach relies on its simplicity, although the resulting nanocomposites may exhibit inhomogeneity in terms of morphology and fillers distribution in the polymer matrix [10,129].…”
Section: Chemical Reduction (In Situ Method)mentioning
confidence: 99%
“…example, Brust and co⁻workers have described the preparation of Ag loaded agarose hydrogels, in which the metallic nanofillers are trapped inside the polymer network due to the agarose capability to dry and rehydrate. In this particular case, the use of agarose as polymeric matrix provides the formation of a recyclable SERS substrate, in which the 1-naphthalenethiol used as analyte can be washed out by dialysis and the composite can be reused again [60] Nanocomposites containing gelatin [61,76,77], natural rubber [73] and distinct synthetic polymers [98][99][100][101] have been also prepared using in situ methods. For instance, Wu and his team have reported the fabrication of Ag loaded poly(styrene) microspheres using the chemical reduction method for the SERS detection of organic molecules such as dyes.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…These images were obtained from natural rubber samples with gold nanoparticles using scanning electron microscopy (SEM). [5,6] presents the green synthesis of gold nanoparticles using natural rubber membranes, an organic component that acts as a reductant/stabilizer. Gold nanoparticles were reduced in natural rubber at different time periods: 6, 9, 15, 30, 60 and 120 min.…”
Section: Dataset Of Photomicrographsmentioning
confidence: 99%
“…In fact, latest years have witnessed growing interest in the fabrication of flexible plasmonic substrates for noninvasive sensing. The research on flexible plasmonics is quickly moving toward the fabrication of low‐cost devices for daily‐life applications and recent studies have reported the fabrication of flexible SERS substrates made of membranes of natural rubber and polydimethylsiloxane containing gold nanoparticles, of silver nanoparticles embedded in polycarbonate plastic films and of hard thermoplastic polymers coated by thin gold or silver layers by sputtering and electroless deposition …”
Section: Introductionmentioning
confidence: 99%